On the determination of interlaminar fracture toughness of carbon/epoxy cross-ply composites - P. Ashok Kumar* , P. Ravinder Reddy , AVSSKS. Gupta (International Journal of Emerging Trends in Science and Technology, 2017)
Delamination between layers is a dangerous failure mode in fiber reinforced composite laminates. Pure mode I tests were conducted to determine the interlaminar fracture toughness, using 16-ply DCB specimens prepared from carbon/epoxy unidirectional fabric, under quasi-static condition. Analysis of the test specimens in terms of mode I interlaminar critical strain energy release rate, GIc showed good agreement between data reduction methods based on modified beam theory, compliance calibration, and modified compliance calibration. The results showed that the measured GIc values at initiation for [0/90]4s specimens are higher than that of unidirectional [00 ]16 specimens.